Impacts of Salinity and Oxygen on Particle-Associated Microbial Communities in the Broadkill River, Lewes DE - Yoshimura, Kristin M.; York, Joanna; Biddle, Jennifer F. (Frontiers in Marine Science, 2018)
Particulate matter in estuarine systems hosts microbial communities that can impact biogeochemical cycles. While the bacterial community composition on suspended particles has been previously investigated, especially with regards to how salinity may structure these communities, the archaeal fraction of the microbial community has not received the same attention. Here we investigate both the bacterial and archaeal community composition on two sizes of particles along a riverine discharge gradient in the Broadkill River, DE, USA, to determine whether the archaeal community is selected by similar environmental stressors as the bacteria. We measured salinity, nutrients, and diatom abundances, and use particle size as a proxy for oxygen concentrations. We show that salinity is a strong environmental factor that controls both bacterial and archaeal community composition and oxygen is an additional factor, impacting archaea more than bacteria.